THE INFLUENCE OF SUSTAINABLE TECHNOLOGY, ABSORPTIVE CAPACITY ON SMES' INNOVATIVE PERFORMANCE THROUGH ECO-INNOVATION IN CULINARY SMES' IN EAST JAVA - Yudiarto Perdana P,; Manuel Goncalves,; Gandung Satriyono,; Ana Komari, (Journal of Innovation Research and Knowledge, 2024)
The great potential of culinary SMEs in East Java is still experiencing obstacles in aspects of technology, product quality, synergy, and infrastructure. This research uses a quantitative intervening model with Sustainable Technology (X1), Absorptive Capacity (X2), Eco-Innovation (Z), and Innovative Performance SMEs (Y) to improve the innovative performance of culinary SMEs in a sustainable manner. The test results show that Sustainable Technology has a significant effect on the innovative performance of SMEs, while Absorptive Capacity and Eco-Innovation do not have a significant effect. Therefore, strategies are needed such as investing in sustainability technology, building connectivity of computing services, providing product research and development programs, collaborating with local communities and related culinary industry players, and ensuring the cleanliness and safety of culinary SME products. By implementing this strategy, it is hoped that culinary SMEs in East Java can improve their innovative performance and business sustainability, so that they can compete in an increasingly competitive market